COMPETITIVE ADVANTAGE THROUGH NEW PRODUCT DEVELOPMENT CAPABILITIES - Hamid, Fahad; ABBASI, MUHAMMAD UMAIR (Archives of Business Research, 2020)
Why are some businesses exceptional in development of new products? In this study, we will discuss various factors which contribute the success of new product development. New product development is the backbone of an innovative organization, the process is built on the solid foundations of capabilities such as network, technology, innovation, and strategic orientation and social capability are the success drivers in the development of new product. The main purpose is to understand the customer need and develop the product by using these capabilities to innovate something which can give value to the customers and achieve competitive edge over competitors. This article discusses about how successful firms use these new product development process capabilities to achieve competitive advantage in the conduct of business.